2015
DOI: 10.1517/17425247.2016.1102224
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable nanocomposite microparticles: preparation, characterization and factors affecting formulation

Abstract: Nanocomposite microparticles have been found to be superior to both nanoparticles and microparticles and may represent a promising carrier for pulmonary drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 117 publications
1
13
0
Order By: Relevance
“…Patients with respiratory disorders are usually administered their medications via inhalation 1. Pulmonary drug delivery offers several merits including its ability to attend higher drug levels at the site of its action, the lung, without the induction of systemic side effects 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with respiratory disorders are usually administered their medications via inhalation 1. Pulmonary drug delivery offers several merits including its ability to attend higher drug levels at the site of its action, the lung, without the induction of systemic side effects 2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, local direct delivery of the drug into the airways is capable of creating fast onset of action with high therapeutic ratio 3. However, the airway geometry of the lungs poses a challenge for delivery into the alveoli 1…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary delivery via inhalation is a common technique of drug administration to patients with a variety of lung diseases. But the airway geometry of the lungs poses a challenge for delivery into the alveoli [14,15] . However, delivery of individual nanoparticles to the lungs appears to be a problematic, as due to their small sizes (< 1μm) which increased their probability of exhalation before deposition [16] .…”
Section: Targeted Inhalable Nanoparticle For Lung Carcinomamentioning
confidence: 99%
“…The differences between microparticles and nanoparticles extend beyond just the size, having larger surface area to volume ratios. Nanoparticles can have a higher drug loading capacity, using less polymers, better cross permeability barriers, increased cellular uptake, longer lung retention and in airway nanoparticles have better chances of mucus penetration [14] . This improves dissolution properties where decreasing the particle size increases the solubility and intracellular drug delivery potential.…”
Section: Dry Powder Inhalers and Nanoparticulate Powders For Inhalationmentioning
confidence: 99%
“…Hygroscopicity and moisture retention are two important factors in hydrogel for clinical medicine application. [33][34][35] Previous study revealed that the Cu-MOP hydrogel was formed based on forming hydrogen bonds between Cu-MOPs and water molecules. Unfortunately, the ability of Cu-MOP hydrogel to maintain moist microenvironment was only for a very short time.…”
Section: Hygroscopicity and Moisture Retention Of The Paa-cu-mop Hydrogelmentioning
confidence: 99%